Financial Accounting for Decision Makers - Peter Atrill; Eddie McLaney (Harlow, England Pearson, 2019)
With a comprehensive and accessible introduction to the subject, Financial Accounting for Decision Makers focuses on the ways in which financial statements and information can be used to improve the quality of decision making. The practical emphasis throughout the book ensures the material is always relevant, whilst the authors' style of introducing topics gradually and explaining technical terminology in a clear, friendly style caters for all students, whether on specialist accounting or non-specialist business degrees. Key features: Updated and expanded examples from the real world demonstrate practical applications and the value of key concepts and techniques. Interactive 'open-learning' style, ideal for self-study, encourages you to check your progress continually. Coverage of developments to the International Financial Reporting Standards (IFRS) including an update to the discussion of the Conceptual Framework for Financial Reporting. Recent changes to corporate governance provisions are explained. Chapter 12 now includes more detail about the role of the auditor. Activities and exercises which enable you to constantly test your understanding and reinforce learning. Key terms, glossary and bulleted summaries providing excellent revision aids.
Keywords: Accounting; Finance; Textbooks; (MGT-104) Fundamentals of Financial Decision-Making